WEB DESIGN BASED ONLINE MANAGEMENT SYSTEM AT 3 MEDAN JUNIOR HIGH SCHOOL - Siti Aisyah; Widia Sari Zebua; Rupiah Boru Tambunan; Lina Sari Damanik; Rut Julianti Hutagalung; Matthew Thompson (INFOKUM, 2021)
This research is entitled Design of Web Based Online Management System at Nasrani 3 Medan Junior High School. The purpose of this research is to design a support system in order to assist prospective students in the reegistration process for Nasrani 3 Medan Junior High School. The method used in this research is a descriptive research method and the waterfall method in the system development methodology used. The result of this research indicate the following conclusions; 1. The system at Nasrani 3 Medan Junior High School is still done manually so that the system built can accelerate academic data processing. 2. The system built can be carried out efficiently on academic performance so that the time required is not too long. 3. All students data, teachers, tuition fees, and student grades are stored in the designed system.